(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The horse played an important role in the life of nomadic pastoral peoples. The article examines the existing opinions about the first centers of domestication of horses. Materials testifying to the domestication of the horse in the Neolithic era, found in Sazagon I, Sazagon II, Zamichatash , Nizhny Zeravshan , Tuzkon and other monuments, indicate that Central Asia was one of the first regions where the horse was domesticated. Historical sources indicate that on the territory of Central Asia there were breeding centers for thoroughbred horses such as "golden horses of Bactria" and " Ferghana heavenly horses".